NOMINATIVE FIELD OF THE CONCEPT “FOOT/OYOQ” IN ENGLISH AND UZBEK (Scientific journal of the Fergana State University, 2023)
The article deals with the study of the linguistic picture of the nominative field “foot/oyoq”, characteristics and the relations of the constituent units of the field in English and Uzbek. Empiric observations showed that the semantic structure and linguistic forms of expression differ from nation to nation. Our studies let us discover the following verbalizers in English and Uzbek: lexemes (words, phraseological units, paremies), syntaxemes (word combinations, sentences, micro and macro texts) and paralinguistic means. Among parts of speech the verb is considered to be the dominant in English and Uzbek. Statistic and componential analysis showed that word combinations (phrasemes) occupy the center of the field as the dominant, phraseological units, sentences and words – the central, morphemes, texts, proverbs and sayings, paralinguistic means the periphery zone of the field. The results say that English and Uzbek languages have their own mode of categorization and conceptualization which is based on the historical and national traditions and we can conclude that determining the nominative field is the primary task in the study of the semantic relations of the units that make it up.